Geochemistry of Tungsten - Helsen, Jan N.W. (My University, 1970)
Chan and Riley (1967) developed a colorimetric method for the determination of tungsten in natural waters and silicate rocks. Applied to silicate rocks this method contains the following stages: evaporation of silica with hydrofluoric acid, co-precipitation of tungsten and some other elements, with hydrous manganese dioxide and cation-exchange separation of vanadium, molybdenum and tungsten. When applying this method on standard solutions and the new U.S.G.S. standard rocks, the results obtained are lower than those suggested by the authors. The results obtained recently with neutron activation analysis of the same standard rocks by Johansen and Steinnes (1970), although different from the results of the present work, also disagree with Chan and Riley. The method was abandoned since a tungsten loss is believed to occur throughout the procedure.
Keywords: colorimetric, tungsten, geochemistry, silicate, rocks